2023
DOI: 10.3390/polym15224456
|View full text |Cite
|
Sign up to set email alerts
|

Obtention and Study of Polyurethane-Based Active Packaging with Curcumin and/or Chitosan Additives for Fruits and Vegetables—Part I: Analysis of Morphological, Mechanical, Barrier, and Migration Properties

David Ruiz,
Yomaira L. Uscátegui,
Luis Diaz
et al.

Abstract: Several polyurethane-formulated films with curcumin and/or chitosan additives for food packaging have been previously obtained. The study examines the effect of the additives on the film’s morphological, mechanical, barrier, and migration properties. Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), water contact angle, thermogravimetric and differential thermal analysis (TGA and DTGA), differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMTA), oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…As evidenced by Table 1, chitosan film exhibits exceptional resistance to oxygen, comparable to commercially available polyvinylidene chloride film (Valenzuela et al 2015). The molecular weight and solvent of chitosan can influence the oxygen permeability of its film (Ruiz et al 2023).…”
Section: Characteristics Of Pure Chitosan Filmmentioning
confidence: 89%
“…As evidenced by Table 1, chitosan film exhibits exceptional resistance to oxygen, comparable to commercially available polyvinylidene chloride film (Valenzuela et al 2015). The molecular weight and solvent of chitosan can influence the oxygen permeability of its film (Ruiz et al 2023).…”
Section: Characteristics Of Pure Chitosan Filmmentioning
confidence: 89%
“…Since isocyanates in polyurethane raw materials are toxic, the safety of polyurethane packaging materials in terms of migration rate is more favorable for the application of polyurethane materials in food packaging. This was considered in a recent study by Ruiz et al [57], where the team used curcumin and chitosan as additives bonded in the network structure of polyurethane. Through testing, they found that although the molecular weight of curcumin was lower than that of chitosan, the physical interaction between curcumin and polyurethane exhibited better compatibility, leading to a reduction of overall migration.…”
Section: Curcumin-based Polyurethanes For Medical Usementioning
confidence: 99%